Secondary traumatization, psychological stress, and resilience in psychosocial emergency care personnel - Greinacher, Anja; Nikendei, Alexander; Kottke, Renate; Wiesbeck, Jürgen; Herzog, Wolfgang; Nikendei, Christoph (International journal of environmental research and public health, 2019)
Volunteers active in psychosocial emergency care offer psychological first aid to survivors of accidents and trauma, their relatives, eye witnesses, bystanders, and other first responders. So far, there are no studies that investigate the secondary and primary traumatization of this group of first responders. We included N = 75 volunteers, who filled out questionnaires to assess their secondary (QST/FST) and primary traumatization (PDS), and levels of comorbid psychological stress (PHQ-9, GAD-7, SF-12). We investigated factors of resilience by measuring attachment behavior (ECR-RD, RQ-2), level of personality functioning (OPD-SFK), sense of coherence (SOC-29), social support (F-SozU), and mindfulness (MAAS). The volunteers' levels of secondary and primary traumatization were below cut-off scores. Their levels of comorbid psychological stress were comparable to representative norm samples. Additionally, the volunteers presented high levels of resilience. Gender (β = 0.26; p < 0.05), case discussions (β = -0.37; p < 0.05), and social support (β = 0.45; p < 0.01) were revealed to be predictors of secondary traumatization, while mindfulness turned out to be a predictor of primary traumatization (β = -0.34; p = 0.008). However, we cannot rule out that the low prevalence of traumatization and comorbid psychological stress in our study sample might not be explained by a positive response bias.